Abandoned : America's lost youth and the crisis of disconnection - Kim, Anne (Journalist) (The New Press, 2020)
A deeply affecting expose of America's hidden crisis of disconnected youth, in the tradition of Matthew Desmond and Adrian Nicole LeBlanc For the majority of young adults today, the transition to independence is a time of excitement and possibility. But 4.5 million young people or a stunning 11.5 percent of youth aged sixteen to twenty-four experience entry into adulthood as abrupt abandonment, a time of disconnection from school, work, and family. For this growing population of Americans, which includes kids aging out of foster care and those entangled with the justice system, life screeches to a halt when adulthood arrives. Abandoned is the first-ever exploration of this tale of dead ends and broken dreams. Author Anne Kim skillfully weaves heart-rending stories of young people navigating early adulthood alone, in communities where poverty is endemic and opportunities almost nonexistent. She then describes a growing awareness including new research from the field of adolescent brain science that "emerging adulthood" is just as crucial a developmental period as early childhood, and she profiles an array of unheralded programs that provide young people with the supports they need to achieve self-sufficiency. A major work of deeply reported narrative nonfiction, Abandoned joins the small shelf of books that change the way we see our society and point to a different path forward.